The rs1634330 Polymorphisms in the SOST Gene Are Associated with Body Composition in Chinese Nuclear Families with Male Offspring - Luyue Qi; Lianyong Liu; Li Li; Weiwei Hu; Wenzhen Fu; Ji Hu; Youjia Xu; Zhenlin Zhang (International Journal of Endocrinology, 2021)
Objective. The purpose of this study was to explore the effect of the SOST gene polymorphisms on body composition in Chinese nuclear families with male offspring. Methods. 1,016 individuals were recruited from 335 Chinese nuclear families with male offspring. The nuclear families consist of at least one male offspring aged 18 to 44. We genotyped the 10 tagged single-nucleotide polymorphisms (SNPs) in SOST gene (rs7220711, rs865429, rs851057, rs1708635, rs2023794, rs1234612, rs74252774, rs1634330, rs851058, and rs1513670) in all the above people. We used dual-energy X-ray absorptiometry to measure the composition of the human body. The quantitative transmission disequilibrium test (QTDT) was used to analyze the associations of the SNPs with the body composition. Results. QTDT analysis showed that rs1634330 was significantly associated with trunk LM P<0.05. However, haplotypes were not found to be significantly associated with the body composition in the within-family association. The 1000 permutations were consistent with these within-family association results. Conclusions. Our results showed that the genetic variation in the SOST gene may contribute to variations in the body composition of Chinese male offspring.